Direito natural e iluminismo no direito português do final do antigo regime - Cabral, Gustavo César Machado (2011)
This thesis aims at investigating how Portuguese Law in the end of Ancient Regime was related to the modern doctrines of Natural Law and to the Enlightened Absolutism of the second half of the eighteenth century. Besides specific literature on the subject, in which are included writings of that time, collections of Statutes and judicial decisions were largely used. At the beginning of this work, the main purpose was introducing the Portuguese political, economic, cultural and juridical context and then showing the philosophical changes of the concept of Natural Law on the works of Hugo Grotius and Samuel von Pufendorf and the emergence of the usus modernus pandectarum. This is important to clarify that, during the kingship of Joseph I and the government of Marquis of Pombal (1750-1777), Law was a fundamental instrument to grant the desire for changing and modernization of Portuguese Crown: it made the King the only source of law-making, which consolidated his power. In order to regulate the use of Roman Law, some powers were granted to the Casa da Suplicação, the most important Royal Court at the moment. The reception of Natural Law by legislation, doctrine and by institutions such as the University and the Casa da Suplicação helped the diffusion of liberal ideas in the end of 18th century, which had the same origins of the Enlightened Absolutism: the modern theories of Natural Law. Thus, the reforms in the Ancient Regime in its last decades contributed to its end, and the Law, mainly Natural Law, had a fundamental importance at this context.